The Implementation of Listening Skill Test Materials Using Moodle to Develop the Listening Skills of Third-Grade Senior High School Students at Nur Al-Falah Islamic Education Institute - Rahman, Rafi Dhaifullah; Sahlani, Sahlani; Kusni, Nikmatullah; Hakim, Lukmanul (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
The development of listening skill test materials using Moodle aims to produce Moodle-based test materials for third-grade Tsanawiyah students at Nurul Falah Islamic Boarding School, to determine the extent of the contribution of Moodle-based instructional media in improving students’ listening achievement, and to identify changes in students’ behavior after using Moodle-based media. The development procedure for the Moodle-based media follows five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The assembled Moodle-based instructional media were then assessed for their effectiveness. Based on the test results obtained from the use of the Moodle-based learning media, the pre-test showed an average score of 63.01, while the post-test average increased to 83.02, indicating a significant improvement. After using Moodle-based instructional media, students became more active during the learning process and more enthusiastic about participating in subsequent lessons. It is recommended that teachers make greater use of technological instructional media, such as interactive Moodle-based platforms.